Cost utility of penicillin use in primary care for the prevention of complications associated with syphilis - Silva, Roberto Carlos Lyra da; Peregrino, Antonio Augusto de Freitas; Rocco, Regina; Ribeiro, Lilian Reinaldi; Machado, Daniel Aragão; Silva, Carlos Roberto Lyra da (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: Despite penicillin being the drug of choice for the treatment of syphilis, many pregnant women who test positive for syphilis do not receive the drug as recommended by the Ministry of Health, contributing to the increase in costs associated with congenital syphilis. Objective: This study aims to estimate the incremental cost-effectiveness ratio of administering at least one dose of 2.4 million IU of benzathine penicillin in the first trimester of pregnancy as soon as the result of a positive rapid treponemal test performed during antenatal care in primary care units of the Brazilian National Health System. Methods: An analytical model was proposed based on a decision tree. The perspective of the analysis was the one used in The Brazilian National Health System. The clinical outcomes were abortion, prematurity, neonatal death, stillbirth, and congenital syphilis, estimated in terms of disability-adjusted life-years. Only direct costs were considered. Deterministic and probabilistic sensitivity analyses were performed. Results: The model predicted that the most efficient strategy is the one that includes the administration of penicillin in primary care for cases of gestational syphilis. This strategy is more effective, although more costly. The cost per disability-adjusted life-years averted with the use of this strategy was estimated at R$49.79 (US$ 10.67). Conclusion: The prenatal strategy in primary care units that includes the administration of penicillin to pregnant women with syphilis during the first trimester of pregnancy has the greatest potential to be cost-effective.